Dark days and vomit - Hipplewith, Joanne (Murmurations: Journal of Transformative Systemic Practice, 2023)
Exegesis The spoken word piece that follows is from a “withness” sense of us all having mental health, not just those we work with. It is raw, disturbing and provocative. A living assemblage of words, rhythms, sounds, beats, feelings and thoughts that stir. A jigsaw of personal and professional contextual living in and habitation of different and similar landscapes, hxstories and environments. This piece resonates with the near and far, steps and breaths, in settings, books, home and abroad. Relational contexts are performed from inside/outside and outside/inside knowledges. The poem was written in one sitting late in 2022. The rawness of the grammar in places and words combine and create this piece in which a rhythm is created on living substances, a heartbeat, a drum, an urge and whispers.